Pemanfaatan Channel Youtube sebagai Media Dakwah Oleh Masjid Al-Irsyad Surabaya - Rahmat A Abdina (Hikmah, 2023)
The times have made it easier to carry out da'wah activities, especially through social media. One of the most popular social media in Indonesia is Youtube. Al-Irsyad Mosque Surabaya is one of the mosques in Indonesia that has a Youtube channel as a medium for preaching. This study aims to determine the effectiveness of the use of the Youtube channel as a medium for preaching the Al-Irsyad Mosque in Surabaya. This research is a library research with the source of the data is obtained from the content uploaded on the Masjid Al-Irsyad TV channel. The results showed that Al-Irsyad Mosque Surabaya in terms of utilizing the Youtube channel as a propaganda medium was very effective, both in quantity and quality. In quantity, it was found that the contents uploaded through the Masjid Al-Irsyad TV channel have been watched by millions of viewers from all over the world. Meanwhile, in terms of quality, the results of video editing are also considered to attract the interest of the audience. This can be seen from the audience's responses through the positive comments column, both Muslim and non-Muslim viewers.Keywords: Al-Irsyad, Mosque, Da'wah Media, Youtube Channel